Arbitration as a Judicial Guarantee to Attract Investment - علي, غسان (Latakia University Journal - Economic and Legal Sciences Series, 2022)
Due to the great economical development which the world witnessed in the second half of the twentieth century and the early current century, countries, especially developing countries, scrambled to encourage the flow of turnover to manipulate their economical problems and to raise the individual income level. This is to be achieved through eliminating barriers that might hinder the coming of the turnover, providing incentives and temptations and creating suitable investment climate sufficient for the above mentioned flow. Thus, investment contracts have their own privacy -- as they are made between a public side which is the state or any of its public institutions on the one hand and a private foreign side on the other hand, in addition to disputes related to investment between these sides. Each of these sides would try to protect its concerns. All these issues made foreign investment in need of guarantees to protect investment and encourage it at the same time. Arbitration court is one of most important guarantees. It can dispel fears of foreign investors and help countries, particularly developing countries, to attract foreign investments.